2004
DOI: 10.1007/s00264-004-0549-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive unicompartmental knee replacement with a nonimage-based navigation system

Abstract: In a prospective study, two groups of 20 unicompartmental knee replacements (UKR) each were operated either using a CT-free navigation system or the conventional minimal invasive technique. Radiographic assessment of postoperative alignment was performed by long-leg coronal and lateral radiographs. The results revealed a significant difference between the two groups in favor of navigation. In the computer-assisted group, 95% of UKRs were in a range of 4-0 varus (mechanical axis) compared with 70% in the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Navigation has been used to improve the reproducibility of the surgical technique, and it has been extensively demonstrated to be efficient [14,16]. Since then, several studies have confirmed the effectiveness of navigation improving UKA implantation [15,17,22], whereas one article did not show any improvement [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Navigation has been used to improve the reproducibility of the surgical technique, and it has been extensively demonstrated to be efficient [14,16]. Since then, several studies have confirmed the effectiveness of navigation improving UKA implantation [15,17,22], whereas one article did not show any improvement [23].…”
Section: Discussionmentioning
confidence: 99%
“…Computerassisted navigation systems have since been used in the positioning of UKA and the initial results were very encouraging [12][13][14][15][16][17][18]. UKA navigation can be done in two ways: either by navigating only the tibial cut while the femoral cuts are performed using conventional instrumentation based on the tibial cut or by navigating both the tibial and the femoral cuts.…”
Section: Introductionmentioning
confidence: 99%
“…However, a limitation of the original UKA studies was the use of a software application intended for TKA navigation. Subsequently, Perlick et al, in 2004, reported that in navigated UKA, the danger of overcorrection is diminished by real-time information about the leg axis at each step during the operation [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite improved component alignment in TKA using navigation, no clear clinical advantages are demonstrated [11,12]. More obvious clinical advantages may be expected in a more demanding surgery, such as the UKA, where traditional techniques can lead to poor alignment accuracy [13][14][15][16]. In fact, results of a recent meta-analysis suggest that despite longer surgical time, the use of a navigation system in UKA results in more accurate component positioning compared with the conventional implantation method [17].…”
Section: Introductionmentioning
confidence: 99%
“…Computer-assisted navigation has been shown to improve postoperative leg alignment compared to conventional techniques [11]. Navigation generally has been shown to increase the congruency of the planned-versus-achieved leg alignment in corrective lower-limb osteotomies and component positioning in TKA [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%